Accounting And Financial Practice And Research In The Era Of Big Data (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of the study is to present a snapshot of big data academic research in accounting and finance, and to highlight the applications in the organization. The analysis is conducted through information provided by Scopus in the period 2016-2020. Relevant literature is identified and sampled to derive a taxonomy of topics, which are studied from the perspective of a taxonomy of topics. These topics are studied from a quantitative perspective by identifying the volume of scientific production in different parameters such as year of publication, area of knowledge, author or authors, and qualitative by highlighting the analysis of the position shown by different research papers referring to the topic related above. This will help to answer the research question How is the accounting and financial practice and research through the analysis of Big data in the period 2016-2020?